Assessing the causes of conflict and its effect on livelihoods: a study from Bardia National Park and Khata Corridor, Nepal - Nepali, SC (Banko Janakari, 2010)
The ten-year conflict in Nepal can be viewed as the result of ignoring and failing to strengthen the state and nation building through political, economic and social integration. This study aimed to understand and assess the causes of conflict and their effects on livelihoods in and around Bardia National Park, Nepal. Crotty's model has been used to collect the information and conduct non parametric Wilcoxon test. Chi-square test with descriptive tables has been used for data analysis. Causes of conflict based on people's perception revealed that 78% and 45% of the respondents agreed that weak governance was the cause of conflict before and after. 79% and 52% attributed economical instability as a cause while 78% and 49% believed disparity in resource use and distribution as the cause of conflict before and after. The overall impact on livelihoods due to the conflict had a weighted mean range 2.0-2.3, suggesting the medium impact on all the assets. The conditions of livelihood were better before and were negatively affected after the conflict. Studying patterns of armed conflict and their impact in a country like Nepal is not just of historical interest, but also a matter of current concern for development. Key words: Conflict; instability livelihoods; non parametric test DOI: 10.3126/banko.v20i1.3507 Banko Janakari, Vol. 20, No. 1 pp.37-43